Kanker Primer Multipel Metakronus pada Berbagai Organ: Kasus Serial - Putriyuni, Anandia; Khambri, Daan (Faculty of Medicine, Universitas Andalas, 2024)
Multiple primary cancer (MPC) is multiple tumors with synchronous or metachronous occurrence in the same individual. Metachronous tumors are defined as those that occur more than six months after the first tumor is diagnosed. It has been reported two serial cases with metachronous multiple primary cancers. One of the cases was triple metachronous, a combination that has never been previously reported. First case: A 58-year-old woman presented with a lump in her right breast and axilla. Histopathology found an invasive micropapillary carcinoma with many lymph node metastases. Two years later, the patient got a rectal mass biopsy with an adenocarcinoma diagnosis. In one month, the patient got a nodule on the right toe, and the result revealed squamous cell carcinoma with moderate to poorly differentiated. Second case: A 76-year-old woman presented a lump on her left cheek with keratinizing squamous cell carcinoma. The patient had a left breast nodule eight months later, and the diagnosis was invasive carcinoma of no special type. Both patients died within 1 year of the last diagnosis. We revealed two cases of primary cancers with different locations and histopathology. The causes of MPCs are unclear, but they may be related to various factors. Multiple primary cancer patients should be closely followed up for possible growth of other cancers. Interdisciplinary collaboration can guarantee the best possible diagnosis and treatment for the patient. Keywords: metachronous, multiple, primary cancer